THE LANGUAGE POLICIES AND PRACTICES OF THE PHILIPPINES AND THAILAND: INSIGHTS AND LESSONS FOR LANGUAGE PLANNING - Demeterio III, F.P.A.; Liwanag, Leslie Anne L. (Silliman Journal, 2022)
This paper comparatively studies the language policies and practices of the Philippines and Thailand in order to gather insights and lessons for ongoing language planning of both countries, as well as of the other countries of the ASEAN region, and of any other countries that are grappling with the issues and challenges of being multicultural and multilingual or are gearing for regional integration/ cooperation and globalization. The aspects of language policies and practices of the said two countries analyzed by this paper are: [1] the profiles of their language policies and practices, [2] their socio-historical and political contexts, [3] their underpinning motivations, [4] their implementations and their structural/ organizational mechanisms, [5] their implications on nationalism and multiculturalism, [6] their implications on the development of human and intellectual capitals, and [7] their implications on regional integration and globalization.